Absence, deviance and unattainable ideals – Discourses on vegetarianism in the Swedish school subject Home and Consumer Studies. (October 2016) - Bohm, Ingela; Lindblom, Cecilia; Åbacka, Gun; Bengs, Carita; Hörnell, Agneta
Objective: This study aimed to describe Discourses on vegetarian food in the Swedish school subject Home and Consumer Studies. Design: The study involved the observation of naturally occurring classroom talk, with audio recording and in some cases video-taping. Setting: The study was conducted during Home and Consumer Studies lessons in five different northern Swedish schools. Method: Fifty-nine students and five teachers were observed, recorded and in some cases video-taped. The resulting data were analysed with a focus on big 'D' Discourses. Results: Results indicated that gendered Discourses of absence, deviance and unattainability restricted some students' access to vegetarian food. The absence of meat was constructed as simultaneously healthy and unhealthy, a lack of cultural familiarity with vegetarian cooking made finding recipes difficult and students perceived the loss of taste as very negative. The vegetarian was seen as deviant, with vegetarianism being conceptually equated with sickness. Access to meat-free food required a commitment to a vegetarian lifestyle, and this was seen as a sacrifice and as too much work, not only for the individual but also for others. Conclusion: To counteract the restricted access to vegetarian food, Home and Consumer Studies teachers can redesign activities in the subject with the help of critical food literacy. For example, cooking could focus on popular plant-based dishes instead of 'empty' vegetarian themes, all students could be allowed to share vegetarian dishes instead of reserving them for vegetarians, the possibly strict rules of vegetarianism could be relaxed for those who do not wish to commit to them and vegetarian food could be deliberately connected to strength and masculinity. However, this presupposes sufficient economic resources and ample food storage space.